Resistance Narratives: A study of H. M. Naqvi’s Home Boy - Fikret Güven (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi, 2019)
The present paper analyzes H. M. Naqvi’s Home Boy as counter-narrative to Orientalism in Western discourse that writes back to the American Empire apropos September 11 and terrorism. Naqvi tries to analyze, describe, problematize and destabilize Orientalist discourse of “othering” a and “stereotyping” The narrative protests against American imperialism—its belligerent foreign policy, its suppression and exploitation of third world countries, interference in other countries, and occupation and invasion of foreign lands. The narrative starts as a typical immigrant narrative in which the protagonist comes to the United States in pursuit of the American dream of prosperity, happiness and freedoms. Initially, the protagonist has assimilative and accommodative tendencies in the hopes of partaking in the economic and social privileges bestowed by a prestigious American education and lucrative employment in big financial institutions in the metropolis. However, the events of September 11 exacerbate an already precarious atmosphere of discrimination that exists in the novel in which their protagonist is treated as an outsider and enemy.